Experimental Study on the Bending Mechanical Properties of Socket-Type Concrete Pipe Joints - Xu Liang; Jian Xu; Xuesong Song; Zhongyao Ren; Li Shi (Buildings, 2024)
In modern infrastructure construction, the socket joint of concrete pipelines is a critical component in ensuring the overall stability and safety of the pipeline system. This study conducted monotonic and cyclic bending loading tests on DN300 concrete pipeline socket joints to thoroughly analyse their bending mechanical properties. The experimental results indicated that during monotonic loading, the relationship between the joint angle and bending moment exhibited nonlinear growth, with the stress state of the socket joint transitioning from the initial contact between the rubber ring and the socket to the eventual contact between the spigot and socket concrete. During the cyclic loading phase, the accumulated joint angle, secant stiffness, and bending stiffness of the pipeline interface significantly increased within the first 1 to 7 cycles and stabilised between the 8th and 40th cycles. After 40 cycles of loading, the bending stiffness of the joint reached 1.5 kN·m2, while the stiffness of the pipeline was approximately 8500 times that of the joint. Additionally, a finite element model for the monotonic loading of the concrete pipeline socket joint was established, and the simulation results showed good agreement with the experimental data, providing a reliable basis for further simulation and analysis of the joint’s mechanical performance under higher loads. This study fills the gap in research on the mechanical properties of concrete pipeline socket joints, particularly under bending loads, and offers valuable references for related engineering applications.